Durability of single-dose rVSV-ZEBOV vaccine responses: what do we know? - Angela Huttner; Claire-Anne Siegrist (Taylor & Francis Group, 2018)
Introduction: The live-attenuated recombinant vesicular stomatitis virus vaccine expressing the glycoprotein (GP) of Zaire Ebola virus (rVSV-ZEBOV) has proven immunogenic in humans and effective in field studies. Yet long-term durability of vaccine responses is unknown. Areas covered: We survey the evidence available in the literature for the durability of human responses to rVSV-ZEBOV. We also review determinants of initial responses and of their persistence. Expert commentary: Persistence of EBOV-GP-specific antibody responses is strong at 2 years - currently the longest post-vaccination interval studied - after a single injection. Vaccine dose predicts persistence of seropositivity, though the magnitude of antibody responses at later time points becomes less dose-dependent. Vaccine-related arthritis is a significant predictor of both persistence and magnitude of the antibody response.